Detailed assessment of night shift work aspects and potential mediators of its health effects: the contribution of field studies - van der Grinten, Tara; van de Langenberg, Daniella; van Kerkhof, Linda; Harding, Barbara N.; Garde, Anne Helene; Laurell, Caisa; Vermeulen, Roel; Peters, Susan; Vlaanderen, Jelle (Frontiers in Public Health, 2025)
Night shift work has been associated with adverse health outcomes, but inconsistencies in epidemiological findings reveal gaps in understanding the mechanisms involved. Beyond shift schedules (e.g., duration and intensity) and nighttime light exposure, we propose assessing ten key aspects to enhance understanding of shift work’s nature and health implications. These include: (1) exposure-related factors (“meal timing and composition during the night shift,” “physical activity during the night shift”); (2) potential mediators (“supplements and medication use,” “social disruption,” “sunlight exposure,” “meal timing and dietary patterns outside shifts,” “physical activity,” “sleep quality,” and “substance use”); and (3) effect modifiers (“occupational co-exposures”). Recent advances in technology, such as mobile apps, wearable sensors, and biomarkers, enable real-time, multidimensional assessments of these factors in field studies. Incorporating these tools into high-quality data collection can provide critical insights into the pathways linking night shift work and health. Such approaches will generate new hypotheses and inform the design of next-generation cohort and case–control studies, fostering a deeper understanding of this complex exposure and its health implications.